IMPLEMENTASI SISTEM EVALUASI KINERJA GURU BERBASIS DIGITAL RUANG GTK UNTUK MENINGKATKAN KINERJA GURU DI SMP IT AL-FATH CIBITUNG - Pradityas Novarani, Niken; Astuti Darmayanti; Chairil Fajar Hadiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the implementation of a digital-based teacher performance evaluation system through Ruang GTK at SMP IT Al-Fath Cibitung, including its supporting and inhibiting factors. The study employed a qualitative approach with a descriptive case study design. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed through data condensation, data display, and conclusion drawing. Data credibility was strengthened through source and technique triangulation. The findings indicate that the implementation of Ruang GTK was supported by effective communication, adequate resources, implementers’ commitment, and a clear division of responsibilities. The main obstacles included limited user accounts, login and synchronization problems, adaptation to system updates, and dependence on internet stability. Ruang GTK helped make teacher performance evaluation more systematic, well-documented, transparent, and accountable. It also supported clearer performance targets, reflection, coordination, and follow-up actions, although this study did not measure its causal effect on learning outcomes. The school is advised to strengthen technical assistance, accelerate account administration, and improve the reliability of its digital infrastructure.